MODIFICATION OF TWO POLES SINGLE PHASE INDUCTION MOTOR AS WIND PICO GENERATOR - Fauzun Atabiq; Budiana Budiana; Arif Febriansyah Juwito; Irfan Syahri; Ihsan Saputra (JURNAL INTEGRASI, 2019)
As an alternative energy, the potential of wind power in Indonesia is quite high. Some of the constraints of wind power include the presence of intermittent winds, the average wind speed in the Indonesian is relatively low, or only certain areas that have moderate to high wind speeds, so that winds that are not too tight can cause the turbines not spinning. This study is about modifying a two pole single phase induction motor as a wind pico generator. Modifications made to the squirrel cage rotor induction motor become two poles axial flux permanent magnet rotors. The test results show that a two pole pico generator is not suitable to be applied to wind power units. Electric power produced by high-speed prime mover, above 1000 rpm only 2.53 Watts. Whereas when it is operated at low speed, less than 200 rpm, the maximum output power power only 44 mW.